2016
DOI: 10.3892/mmr.2016.5639
|View full text |Cite
|
Sign up to set email alerts
|

Endogenously synthesized n-3 fatty acids in fat-1 transgenic mice prevent melanoma progression by increasing E-cadherin expression and inhibiting β-catenin signaling

Abstract: Malignant melanoma is the most lethal form of skin cancer. Although preclinical studies have shown that n-3 polyunsaturated fatty acids (PUFAs) are beneficial for prevention of melanoma, the molecular mechanisms underlying the protective effects of n‑3 PUFAs on melanoma remain largely unknown. In the present study, endogenously increased levels of n-3 PUFAs in the tumor tissues of omega‑3 fatty acid desaturase (fat‑1) transgenic mice was associated with a reduction in the growth rate of melanoma xenografts. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
0
8
0
1
Order By: Relevance
“…Similarly, it was found that increasing the endogenous levels of n-3 PUFA, using n-3 fatty acid desaturase (fat-1) transgenic mice, was associated with a reduction in the growth rate of melanoma xenografts. This reduction in melanoma growth in fat-1 mice, compared with wild-type mice, was associated with an increased expression of E-cadherin and the reduced expression of its transcriptional repressors, Zeb-1 and Snail-1 (293). It also significantly repressed the EGFR/Akt/β-catenin signalling pathway and induced the formation of significant levels of anti-inflammatory n-3 PUFA-derived lipid mediators, such as resolvin D2 and E1, maresin 1 and 15-hydroxyeicosapentaenoic acid (293).…”
Section: The Perspectives Of Using Dietary Lipids For An Integrated Smentioning
confidence: 93%
“…Similarly, it was found that increasing the endogenous levels of n-3 PUFA, using n-3 fatty acid desaturase (fat-1) transgenic mice, was associated with a reduction in the growth rate of melanoma xenografts. This reduction in melanoma growth in fat-1 mice, compared with wild-type mice, was associated with an increased expression of E-cadherin and the reduced expression of its transcriptional repressors, Zeb-1 and Snail-1 (293). It also significantly repressed the EGFR/Akt/β-catenin signalling pathway and induced the formation of significant levels of anti-inflammatory n-3 PUFA-derived lipid mediators, such as resolvin D2 and E1, maresin 1 and 15-hydroxyeicosapentaenoic acid (293).…”
Section: The Perspectives Of Using Dietary Lipids For An Integrated Smentioning
confidence: 93%
“…Autophagy inhibition suppressed apoptosis, and autophagy induction further enhanced apoptosis in response to DHA treatment (Jing et al, 2011). There is evidence that n-3 PUFA may inhibit the expression of EMT markers and reduce associated invasive properties in cancer cells (D'eliseo et al, 2016;Yin et al, 2016). Altogether, these effects could bring beneficial values to delay the appearance/diagnosis of a primary tumor and as such be of interest in primary prevention.…”
Section: Na V a As Targets For Nutritional Management Of Cancersmentioning
confidence: 99%
“…Dr. Jing X. Kang, who is director of the Harvard Center for Fatty Acid Research, noted that fatty acids, as well as vitamins and amino acids, are one of the most important nutrients in the human body. PUFAs ω-3 are one of two essential fatty acids that the human body cannot synthesize and that must enter the body with food, and the other -ω-6 fatty acids (Meester & Watson, 2008;Delpech et al, 2015;Liu et al, 2014;Luo et al, 2021;Wu et al, 2016;Yin et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%